Upregulation of miR-146a contributes to the suppression of inflammatory responses in LPS-induced acute lung injury. (1st September 2013) - Zeng, Zhenguo; Gong, Honghan; Li, Yong; Jie, Kemin; Ding, Chengzhi; Shao, Qiang; Liu, Fen; Zhan, Yian; Nie, Cheng; Zhu, Weifeng; Qian, Kejian
ABSTRACT: Despite the critical role of microRNA in inflammatory response, little is known about its function in inflammation-induced Acute Lung Injury (ALI)/Acute Respiratory Distress Syndrome (ARDS). To investigate the potential role of microRNA146a (miR-146a) in ALI, we used lipopolysaccharide (LPS)-induced ALI rat model. Our data revealed that LPS-induced lung injury in rats resulted in significant upregulation of proinflammatory cytokine tumor necrosis factor-alpha (TNF-α), IL-6, IL-1β, and miR-146a expression. LPS treatment also leads to higher expression of miR-146a as well as increase in secretion of TNF-α, IL-6, and IL-1β in alveolar macrophage (AM) NR8383 cells in a time-dependent manner. Manipulation with miR146a mimic significantly suppressed LPS-mediated TNF-α, IL-6, and IL-1β induction in NR8383 cells by repressing expression of IRAK-1 and TRAF-6. These data clearly indicate that the upregulation of miR146a suppresses inflammatory mediators in LPS induced-ALI model. Therefore, miR-146a may be therapeutically targeted as a mean to repress inflammatory response following ALI.